SMEs’ Sustainability: Between Business Resilience and Business Growth, Which One is More Significant in The Time of Crisis? - Galih Adi Prastian; Agus Setiawan; Nia Kurniati Bachtiar (Jurnal Manajemen Bisnis, 2022)
This article discussed two most important variables for business sustainability which were business resilience and business growth, then measured which variable is need to be pursued more than other. We also applied Digital Busines Model (DBM) as moderating role. By doing so, we expect that we can measure the role of DBM to modern business and how it strengthens and faster the resilience and growth process in business sustainability. We found out that business resilience had more influence and worth to pursue than business growth with 0.774 for resilience and 0.413 for growth. This study revealed that there was no moderating effect of DBM to business sustainability either through business resilience or growth, even though both elements had strong direct influence to business sustainability. Finally, this research suggests that in the time of crisis, business needs to focus more to its resilience strategy than pursuing growth to sustain their business.